AN ANALYTICAL STUDY OF PHILOSOPHY IN FUNERALS OF BUDDHISTS IN ROI ET PROVINCE - Khunsaro (Tummuang), Phrakhrupalad Rangsan; bodhikun, Phrakhru Bhavana; Leeka, Jaras; Abhivaddhano, PhramahaPrateep; Abhitano (Pensuk), Phramaha Jinkamol (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were: 1) to study the funeral arrangements of Buddhists in the Isan region; 2) to study the funeral arrangements of Buddhists in Roi Et Province; 3) to analyze the philosophy of funeral arrangements of Buddhists in Roi Et Province. This study was a qualitative research conducted by studying the information from the Tipitaka, documents and related research. There were 25 key informants. The obtained data were analyzed by descriptive analysis method based on inductive method. The research results were as follows: 1) The funeral rites of Isan people are based on traditions that have been practiced, such as bathing the corpse, dressing for the corpse and tying the ceremonial seal, and inviting monks to perform the requiem ceremony and then filling the body. Also, the body is set for merit making, and bring the body to cremation. Bathing the body and cremating the dead bodies from accidents, death during pregnancy or infant bodies are not practiced but for these, the method of burial is used. 2) Funeral arrangements for Buddhists in Roi Et Province adhere to the beliefs according to the traditions of the northeastern region. Bathing and cremation of the dead bodies from accidents, death during pregnancy or infant bodies are not conducted, the method of burial is used.Keeping the body depends on the status of the relatives, but not more than 3 days, because there is no anti-rotting drug, only lime and tobacco coffin flooring. Nowadays, the bodies are kept in cold coffins, so they are kept for a long time to wait for distant relatives to attend the funeral. 3) Philosophy concepts are as follows: 1) Buddhist metaphysics appears in the chant of Matika-Abhidhamma, which is a recitation of the mind, Cetasika, Rpa, Nibbna; 2) Buddhist epistemology arises from taking what has been obtained from listening to the sermon and taking it into consideration until it becomes a body of knowledge and continually contemplate the dhamma that has been obtained; 3) Buddhist ethics, namely the precepts, people attending funerals will receive precepts for the reconcilia tion of the body and speech; Kusala-Kammapatha 10, which is the reconciliation of the body, speech, and mind, and the development of wisdom by adopting the morals gained from attending the funeral to live with negligence in accordance with the Middle Path Principle.